Assessing Geotouristic Potentials for Developing Sustainable Tourism (A case Study in Tabriz’ Eynali Mountain) - Hejazi, Seyed Asadollah; Javadi, Mahdi; Mokhtari, Davoud (International Journal of Psychosocial Rehabilitation, 2020)
Geotourism is one of the newest concepts within tourism studies today. The popularity of geotourism has likewise grown rapidly over the past few decades. This rapidly growing popularity and the growing body of research on geotourism create the need for a comprehensive review of existing literature on the subject. Geotourism is a kind of tourism in natural areas which pays a special attention to geology and landscapes and also provides background for tourism in geosites and protecting natural diversity and through protection and learning helps the concept of geology science. The present study aims to investigate the effects of geomorphologic phenomena and processes of the region on tourists and geotourisms. The study is descriptive, analytical and field research in method and to collect data library research, documents, maps and instruments such as questionnaire, interview and imaging have been used. Comanescu method used to evaluate the standards of tourism and geomorphologic productivity with the purpose of recognizing geotourist potentials. According to this method scientific, cultural, economic, management and aesthetic values are investigated. The findings out of this study showed that Einali had high potential in tourism, but due to the limitations of this region, tourists neglect it. In the current study, data collected based on the standards of Comanescu method and the questionnaires filled out by geomorphology researchers, scientific professors, PhD students of geomorphology major and also the residents of that region. Among the landforms selected as geosites to attract tourists, Einali Summit gained the maximum tourism points among other geotourist phenomena, due to the high aesthetic value rather than other geomorphosites of Einali. This area attracts many tourists due to plant and animal diversity in spring.